Links between securities settlement systems: An oligopoly theoretic approach - Karlo Kauko (Bank of Finland, 2002)
This paper presents a duopoly model of the securities settlement industry.Because pooling a large amount of payments can help in using liquidity efficiently, issuers prefer systems where a large number of securities are issued.If the central securities depositories establish a mutual link that enables investors to make transactions with foreign securities, cost savings can be achieved. However, these links may have unexpected effects on CSDs' pricing, and the issuers' share of the fee burden can increase substantially.It is not advisable to ban additional fees for using the link, as the CSDs might simply increase the fee for domestic transactions.
URN:NBN:fi:bof-20140807430
Keywords: L13; G20; 330; oligopoly; securities settlement systems